PERUBAHAN MAKNA DALAM BERITA ARAB aljazeera.net - M Wildan Awwiby; Karyani Karyani; Rina Dian Rahmawati (Al-Lahjah, 2021)
This study aims to determine the change in meaning in Arabic news. One of the media that presents news is aljazeera.net, which is a web page that presents news in Arabic and English. Research with this analytical method uses a type of text analysis research to find out changes in meaning in Arabic news sourced from aljazeera.net, with this method we can find out the types of changes in meaning in Arabic news that have been determined. In presenting the news there will certainly be a change in meaning. There are 7 kinds of changes in meaning in linguistics, namely (1) expansion or generalization (2) narrowing of meaning or specialization (3) elevation of meaning or amelioration (4) reduction of meaning or exploration and (5) synesthesia, (6) association and (7) ) metaphor. The results of our analysis show that in one of the news texts published on the Aljazeera.net website there are 5 changes in meaning.